Wide‐angle 2D beam‐steering with Si‐based 16 × (1 × 16) optical phased arrays. Issue 10 (1st May 2020) - Yoon, H.; Lee, D.‐S.; Kim, S.‐H.; Kang, G.; Shim, J.; Rhee, H.; Kwon, N.; Kim, J.‐Y.; Park, H.‐H.
Abstract : The authors demonstrate integrated 1D optical phased arrays (OPAs) for wide‐angle 2D beam‐steering. The 2D OPA consists of 16 1D transversal steering OPAs whose radiators have different grating periods, to assign different longitudinal angles. The transversal steering of each OPA is performed by the phase control of the p‐i‐n electro‐optic phase shifter array. The 1D transversal steering OPAs operate serially, changing the longitudinal radiation angle. The grating radiators were designed with an array pitch of 2 μm, and a varying period in the range of 610–710 nm. The entire 16 × (1 × 16) OPAs were integrated into a small area of 26.5 mm 2 . The obtained transversal/longitudinal beam‐steering range was 46°/44°, respectively, with a wavelength of 1560 nm, which enables wide 2D beam‐steering.